2016
DOI: 10.1016/j.ijgo.2015.10.029
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study comparing surgical outcomes and ultrasonographic evaluation of scarring after laparoscopic myomectomy with conventional versus barbed sutures

Abstract: Laparoscopic myomectomy using CBS is a suitable alternative to TIS in the treatment of uterine myomas for women with up to three tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Tinelli et al [32] in a multicenter retrospective study, with the largest number of patients, investigate clinical outcomes after laparoscopic myomectomy related to the use of traditional interrupted sutures or continuous barbed suture. This trial demonstrated that the use of barbed filaments is a valid opportunity in the treatment of symptomatic myoma during laparoscopic procedure, especially in case of 3 or more uterine myomas.…”
Section: Resultsmentioning
confidence: 99%
“…Tinelli et al [32] in a multicenter retrospective study, with the largest number of patients, investigate clinical outcomes after laparoscopic myomectomy related to the use of traditional interrupted sutures or continuous barbed suture. This trial demonstrated that the use of barbed filaments is a valid opportunity in the treatment of symptomatic myoma during laparoscopic procedure, especially in case of 3 or more uterine myomas.…”
Section: Resultsmentioning
confidence: 99%
“…Another conflicting factor is the type of the suture material. It is widely known that using barbed suture during myomectomy makes the duration of operation shorter with less hemorrhage, and it is shown that using barbed suture has no negative impact on myomectomy scar healing in a multicenter study [10]. In our study, we used both types of the suture and we could not analyze the effect of the suture type on LM complications.…”
Section: Discussionmentioning
confidence: 90%
“…It's widely known that using barbed suture during myomectomy makes the duration of operation shorter with less hemorrhage and it's shown that using barbed suture has no negative impact on myomectomy scar healing in a multicenter study. [10] In our study, we used both types of the suture and we couldn't analyze the effect of the suture type on LM complications.…”
Section: Discussionmentioning
confidence: 99%